YELLOW FEVER PREVENTION STRATEGIES AWARENESS AMONG HIV-INFECTED PATIENTS IN SÃO PAULO, BRAZIL - Avelino-Silva, Vivian Iida; Francelino, Hilario Sousa; Kallás, Esper Georges (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Introduction: Vaccination is the main preventive strategy against Yellow Fever (YF), which is a public health concern in Brazil. However, HIV-infected patients might have insufficient knowledge regarding YF, YF prevention, and vaccines in general. Methods: In this questionnaire-based study, data from 158 HIV-infected individuals were addressed in three distinct outpatient clinics in São Paulo. Information was collected on demographic and clinical characteristics, as well as patients' knowledge of vaccines, YF and YF preventive strategies. In addition, individual YF vaccine recommendations and vaccine status were investigated. Results: Although most participants adequately ascertain the vaccine as the main prevention strategy against YF, few participants were aware of the severity and lack of specific treatment for YF. Discrepancy in YF vaccine (patients who should have taken the vaccine, but did not) was observed in 18.8% of participants. Conclusion: YF is an important and preventable public health concern, and these results demonstrate that more information is necessary for the HIV-infected population.